Near complete deletion of KMT2D in a college student. Issue 5 (18th January 2022) - Gooch, Catherine; Souder, Jaclyn Paige; Tedder, Matthew L.; Kerkhof, Jennifer; Lee, Jennifer A.; Louie, Raymond J.; Sadikovic, Bekim; Fletcher, Robin S.; Robin, Nathaniel H.
Abstract: Pathogenic variants in KMT2D are typically associated with Kabuki syndrome (KS), a rare multisystem disorder. KS is characterized by facial dysmorphisms, intellectual disability, skeletal and dermatoglyphic differences, and poor growth. Seventy percent of individuals with clinically diagnosed KS have a confirmed pathogenic variant in KMT2D or less commonly KDM6A . The majority of mutations found in KMT2D are de novo nonsense or frameshift, with deletions and duplications rarely reported in the literature. Here, we present the case of near complete deletion of KMT2D in a college student with normal intelligence discovered via exome sequencing and EpiSign methylation testing. This case provides evidence that large deletions in KMT2D are compatible with normal intelligence and presents EpiSign as a method for discovering molecular causes of KS not identified by traditional molecular testing.